Fetal echocardiography - DeVore, Greggory R. (London : Porthemon, 1999)
(Producer) Features 548 video clips, more than 150 ill. demonstrating normal and abnormal anatomy, full color images of pathology specimens from 44 cardiac malformations, more than 4,500 interactive activities, 60 full-text articles from medical literature, and more than 180 pathological ultrasound video clips.
[1]. Screening examination of the fetal heart -- [2]. Pathology.
CD is available at Koleksi Media Perpustakaan HUKM
System requirements: 486 processor or Pentium; 16 MB RAM (32 MB recommended); Windows 95, 98, and NT; 2 x CD-ROM (4x recommended); 16-bit graphics card; sd. card.
System requirements: MacOS, PowerPC; 16 MB RAM (32 MB recommended); System 7.5 or higher; 2 x CD-ROM (4x recommended)
Keywords: Fetal Heart -- ultrasonography -- CD-ROM; Fetal Heart -- pathology -- CD-ROM; Echocardiography